FOREIGN EXPERIENCE IN THE APPLICATION OF CUSTOMS INFORMATION TECHNOLOGIES (INNOVATIVE ECONOMY, 2020)
Fradynskyi O.A., Brendak A.I. FOREIGN EXPERIENCE IN THE APPLICATION OF CUSTOMS INFORMATION TECHNOLOGIESPurpose. The aim of the article is research of foreign approaches to the formation and functioning of information technology in the field of customs.Methodology of research. The theoretical basis of the study is international regulations, scientific works of domestic and foreign scientists on the functioning of customs information technologies, official websites of customs administrations. The main results of the study are obtained through the use of a dialectical method of cognition of phenomena that have a legal and economic nature and relate to approaches to the use of information technology in the implementation of customs procedures. In addition, such research methods are used as: analysis and synthesis – when reviewing the latest trends in research; abstract and logical – to form conclusions from the study.Findings. The main advantages of the use of customs information technologies in the field of state customs are outlined. The main provisions of international normative legal and instructive acts are analysed. The example of Singapore and the United States reveals the evolution and functioning of IT systems in the activities of customs services. It is concluded that the focus of Singapore's customs information systems on the simplification of foreign economic activity, in contrast to the US Customs and Border Service, where security accents of IT systems prevail.Originality. The study of foreign experience in the formation and functioning of customs information technologies is further developed, in particular, the recommendations of the World Customs Organization in this area are analysed and the main directions of development of customs information technologies are outlined on the example of Singapore and the USA.Practical value. The obtained results of the research can be used in the practical activity of the divisions of the State Customs Service of Ukraine, the competence of which includes the issues of introduction and practical use of customs information technologies.Key words: customs service, information technologies, customs risks, TradeNet system, World Customs Organization, Kyoto Convention, security, customs procedures.
Keywords: Key words; customs service; information technologies; customs risks; TradeNet system; World Customs Organization; Kyoto Convention; security; customs procedures.